Foreign direct investment, renewable energy and governance in major copper- and lithium-mining countries - Edelina Coayla; Ysabel Bedón; Robert Chávez (Center of Biomass & Renewable Energy (CBIORE), 2026)
Funding the supply of critical materials for the transition to renewable energy (RE) is crucial to addressing climate change. For the world’s leading economies in copper and lithium mining, this paper investigates the association among foreign direct investment (FDI), governance, carbon emissions (CO2) and renewable energy consumption (REC). Using 2002–2023 panel data, a unit root test was applied to determine the stationarity of the variables and cointegration tests revealed cointegration in first differences. The variables were cointegrated at the 1% significance level, as indicated by the Kao Residual Cointegration Test. Next, the fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) panel regression methods were employed. The FMOLS model findings indicated a long-term negative relationship between FDI and RE. Specifically, a 1% increase in FDI (as a percentage of GDP) reduces REC by 0.24% in the major copper- and lithium-producing economies. Governance, measured by control of corruption, has a positive effect on clean energy consumption, and CO2 emissions are significantly negatively associated with REC. Using the DOLS model, we confirmed the robustness of these long-term panel relationships. Policymakers should strengthen the quality of governance, including combating corruption and encouraging FDI in RE. This strategy should also support sustainable mining practices and responsible consumption, aligning with Sustainable Development Goals (SDGs) 7 and 12, respectively.